2022
DOI: 10.1109/access.2022.3164103
|View full text |Cite
|
Sign up to set email alerts
|

Human–Robot Collaboration in 3D via Force Myography Based Interactive Force Estimations Using Cross-Domain Generalization

Abstract: In this study, human robot collaboration (HRC) via force myography (FMG) bio-signal was investigated. Interactive hand force was estimated during moving a wooden rod in 3D with a Kuka robot. A baseline FMG-based deep convolutional neural network (FMG-DCNN) model could moderately estimate applied forces during the HRC task. Model performance can be improved with additional training data; however, collection of it was impractical and time-consuming. Available long-term multiple source data (32 feature spaces) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For compliant collaboration during training and testing, motion trajectories were not fixed between a start and end point; rather, it was bounded by 6-axis rectangular areas in the 1D, 2D, and 3D workspaces [ 51 ]. This allowed flexible dynamic motions within certain ranges, instead of restricted movements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For compliant collaboration during training and testing, motion trajectories were not fixed between a start and end point; rather, it was bounded by 6-axis rectangular areas in the 1D, 2D, and 3D workspaces [ 51 ]. This allowed flexible dynamic motions within certain ranges, instead of restricted movements.…”
Section: Discussionmentioning
confidence: 99%
“…This control mechanism could be implemented to control and monitor large industrial assembly line robots that do not have any joint torque sensors to recognize the external environment. Further description of this pHRI platform can be found in [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, CNN based GAN models are more dominant and have shown good performances in image classifications and pattern recognition. In our previous studies, we found that the model could effectively learn discriminative features of time-series interactive data [16], [17]. In this study, window size of the FMG-DCGAN model was set to 10ms evaluate the smallest time-series input (every single row) in the system.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that intrasession models could estimate applied forces well (accuracies of 94%>R 2 >82%) where training and evaluation were carried out in the same session, had similar feature distributions, and were labeled properly. Recently, adapting domain adaptation, domain generalization and cross-domain generalization techniques enabled an SVR, and a convolutional neural network (CNN) model trained with labeled FMG data from multiple pHRI source domains to recognize applied hand forces in unknown pHRI target scenarios that the model had never seen before [15]- [17]. Finetuning allowed required periodic calibrations to recognize any unseen, instantaneous signals.…”
Section: Introductionmentioning
confidence: 99%